DEMOGRAPHIC DRIVERS AND SOCIAL MEDIA INFLUENCES ON ONLINE SHOPPING PATTERNS: A STUDY AMONG GENERATION Y - Mr. Parvinder Singh Bajwa; Dr. Kanchan Rani (IJRDO - Journal of Business Management, 2025)
This study examines the combined effect of demographic characteristics and social media influences on online shopping patterns among Generation Y consumers in the Indian Tricity region (Chandigarh, Mohali, Panchkula). Utilizing survey data from 500 respondents and applying advanced statistical techniques such as confirmatory factor analysis and structural equation modeling, the research identifies age and occupation as key demographic drivers, while factors like social media trust, call-to-action effectiveness, and content engagement significantly shape purchase behaviour. The findings reveal that the perceived usefulness of social media mediates these relationships, underscoring the importance of clear, reliable, and engaging content in driving digital purchases. These insights address gaps in the literature regarding non-metro urban markets and provide actionable recommendations for marketers to develop targeted, demographic- sensitive social media strategies to enhance online consumer engagement and conversion.